IGF-I, IgA, and IgG responses to bovine colostrum supplementation during training - Mero, A.; Kähkönen, J.; Nykänen, T.; Parviainen, T.; Jokinen, I.; Takala, T.; Nikula, T.; Rasi, S.; Leppäluoto, J. (Journal of Applied Physiology, 2002)
This study examined the effect of bovine colostrum (Dynamic colostrum) supplementation on blood and saliva variables (study 1) and the absorption of orally administered human recombinant insulin-like growth factor (IGF)-I (rhIGF-I) labeled with 123I (123I-rhIGF-I) (study 2). In study 1, adult male and female athletes were randomly assigned in a double-blind fashion to either an experimental (Dynamic; n = 19) or a control (Placebo; n = 11) group. The former consumed daily 20 g of Dynamic supplement, and the latter 20 g of maltodextrin during a 2-wk training period. After bovine colostrum supplementation, significant increases were noticed in serum IGF-I (P < 0.01) and saliva IgA (P < 0.01) in Dynamic compared with Placebo. In study 2, gel electrophoresis was carried out in 12 adult subjects with serum samples taken 60 min after ingestion of 123I-rhIGF-I and showed peaks at 0.6 and at 40-90 kDa, with the former inducing 96% and the latter 4% of the total radioactivity. It was concluded that a long-term supplementation of bovine colostrum (Dynamic) increases serum IGF-I and saliva IgA concentration in athletes during training. Absorption data show that ingested 123I-rhIGF-I is fragmented in circulation and that no radioactive IGF-I is eluted at the positions of free, or the IGF, binding proteins, giving no support to the absorption of IGF-I from bovine colostrum.